The Effectiveness of Problem-Based Learning Methods in Improving Prospective Elementary School Teachers' Critical Thinking Skills - Sisi Harokah; Setiawan Edi Wibowo; Anang Sudigdo; Asep Yudianto; Ika Yuni Wulansari (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractThis research was conducted to uncover the extent to which prospective elementary school teachers can utilize problem-based learning methods to improve their critical thinking skills. We employed a single-group pre-test experimental research approach, incorporating a pre-test and a post-test. 47 prospective elementary school teachers in Sarjanawiyata Tamansiswa University comprise this research sample. The analysis of data used the tests Wilcoxon and N Gain Score. These results show the problem-based learning methods that effectively enhanced the critical thinking of prospective elementary school teachers. The Wilcoxon test results reveal a statistically significant effect of problem-based learning methodologies on the development of critical thinking skills in students, with a sig value of 0.000. The test results for the means of the N Gain Score center on improving critical thinking competence in which their mean score is 0.61 and their average percentage is 61.07. Therefore, using problem-based learning methods will indeed immensely contribute much in enhancing the critical thinking in prospective elementary school teachers.Keywords: problem-based learning, critical thinking, prospective elementary school teachers.AbstrakPenelitian ini dilakukan untuk mengetahui sejauh mana calon guru sekolah dasar dapat memanfaatkan metode pembelajaran berbasis masalah untuk meningkatkan kemampuan berpikir kritisnya. Penelitian ini menggunakan pendekatan penelitian eksperimen pra-tes kelompok tunggal, yang terdiri dari pra-tes dan pasca-tes. Sebanyak 47 calon guru sekolah dasar di Universitas Sarjanawiyata Tamansiswa menjadi sampel penelitian ini. Analisis data menggunakan uji Wilcoxon dan N Gain Score. Hasil tersebut menunjukkan bahwa metode pembelajaran berbasis masalah efektif meningkatkan kemampuan berpikir kritis calon guru sekolah dasar. Hasil uji Wilcoxon menunjukkan bahwa metodologi pembelajaran berbasis masalah berpengaruh signifikan secara statistik terhadap pengembangan kemampuan berpikir kritis siswa, dengan nilai sig sebesar 0,000. Hasil uji rata-rata N Gain Score berpusat pada peningkatan kemampuan berpikir kritis dengan nilai rata-rata 0,61 dan persentase rata-rata 61,07. Oleh karena itu, penggunaan metode pembelajaran berbasis masalah akan sangat membantu dalam meningkatkan kemampuan berpikir kritis calon guru sekolah dasar.Kata kunci: pembelajaran berbasis masalah, berpikir kritis, calon guru sekolah dasar.